COLONIAL HERITAGE: A RESOURCE FOR LOCAL DEVELOPMENT IN EL HARROUCH, ALGERIA - Bouraoui Ibtissem,; Bencherif Meriama, (International Journal of Innovative Technologies in Social Science, 2024)
The small village, which started as a settlement, still maintains a close relationship with its surrounding environment. Its rural origins are still evident, as it aligns with the rhythm of the countryside and offers its services as a relay and mediator in both directions. The town of El Harrouch, located in eastern Algeria, was chosen for its distinct behavior compared to other similar towns. Although it has not undergone any significant changes or transformations, it is situated in an agricultural basin surrounded by high-yield farmland, which limits its spatial growth. Despite its strategic location and historical roots as the oldest settlement in Algeria, urban development has been slow. As a result, the built environment remains in disrepair, especially in the colonial grid that makes up the town center. This legacy, whose advanced deterioration is due to various factors, is the subject of this paper. We aim to explore questions related to the future development of El Harrouch. Can the revitalization of its colonial heritage lead to a local economic dynamic based on the potential and assets of the town? How can all stakeholders, both public and private, participate in new prospects for the town's development? Assuming that the town's agricultural potential is a driving force for development through agrotourism, is this dimension compatible with short- and medium-term planning policies, and do we have the means to balance present needs with future uncertainties?